2022
DOI: 10.1002/bmc.5436
|View full text |Cite
|
Sign up to set email alerts
|

Stability‐indicating liquid chromatography method development for assay and impurity profiling of amitriptyline hydrochloride in tablet dosage form and forced degradation study

Abstract: Amitriptyline hydrochloride is an antidepressant drug with sedative effects used to treat the symptoms of anxiety, agitation with depression and schizophrenia with depression. A reversed‐phase high‐performance liquid chromatography method was developed to separate and quantitatively determine the assay and four organic impurities of amitriptyline in tablet dosage form and bulk drugs using a C18 column in an isocratic elution mode with mobile phase consisting of a mixture of pH 7.5 phosphate buffer and methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The forced degradation study aids in the development of a stability‐indicating liquid chromatographic method and provides information regarding the drug moiety's intrinsic stability, impurity profile (process‐related impurities or degradation‐related products), and degradation pathways [27–50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The forced degradation study aids in the development of a stability‐indicating liquid chromatographic method and provides information regarding the drug moiety's intrinsic stability, impurity profile (process‐related impurities or degradation‐related products), and degradation pathways [27–50].…”
Section: Methodsmentioning
confidence: 99%
“…The authors, thus, focused on developing a new stability‐indicating method employing normal‐phase HPLC for the separation and estimation of D‐Valacyclovir impurity in the Valacclovir drug substance and drug product [27–50]. The chromatographic peaks obtained from placebo (a blend of excipients used in formulation) and diluent, as well as all 14 known impurities, were resolved very well from both the valacyclovir and D‐Valacyclovir.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology that was designed and established as part of the intended investigation was evaluated in accordance with International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) requirements, and the results showed that it was specific, linear, accurate, precise, and robust (ICH, 2005; Narasimha & Chandrasekar, 2019; United States Pharmacopeia, 2021). The results of the forced degradation study proved that the developed HPLC method possesses the stability‐indicating characteristics, in addition to being specific and selective in the separation and quantitative determination of BXM and its organic related impurities in drug substance and drug product (Bakshi & Singh, 2002; Blessy et al, 2014; Boppy et al, 2022; Carr & Wahlich, 1990; Ettaboina, Katakam, & Dongala, 2022; Ettaboina, Nakkala, & Chathalingath, 2022; Katakam, Ettaboina, & Dongala, 2021; Katakam, Ettaboina, & Marisetti, 2021; Lakka & Goswami, 2012; Lakka et al, 2021; Lakka et al, 2022; Lakkireddy et al, 2015; Mohan et al, 2022; Narasimha et al, 2011; Narasimha et al, 2019; Narasimha et al, 2020; Narasimha et al, 2022; Siva et al, 2022; Snyder et al, 2010). In addition, the experimental studies utilizing the LC–MS technique were carried out to evaluate the mass spectral data of newly formed unknown impurities when the sample was subjected to oxidative stress testing.…”
Section: Introductionmentioning
confidence: 99%
“…for the separation and quantitative estimation of S ‐enantiomer of LA from both the drug substance and drug product (tablet dosage form). The stability‐indicating properties of the developed test method were assessed using forced degradation studies (Bakshi & Singh, 2002; Blessy et al, 2014; Boppy et al, 2022; Carr & Wahlich, 1990; Ettaboina, Katakam, & Dongala, 2022; Ettaboina, Nakkala, & Chathalingath, 2022; ICH, 1996; ICH, 2003; Katakam, Ettaboina, & Dongala, 2021; Katakam, Ettaboina, & Marisetti, 2021; Lakka & Goswami, 2012; Lakka et al, 2021, 2022; Lakkireddy et al, 2015; Mohan et al, 2022; Nagulancha et al, 2023; Narasimha et al, 2011, 2019, 2020, 2022; Siva et al, 2022; Snyder et al, 2010). The developed test method was validated in accordance with ICH (International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use) guidelines for specificity, linearity, accuracy, precision, and robustness (ICH, 2005; Narasimha & Chandrasekar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…for the separation and quantitative estimation of S-enantiomer of LA from both the drug substance and drug product (tablet dosage form). The stability-indicating properties of the developed test method were assessed using forced degradation studies (Bakshi & Singh, 2002;Blessy et al, 2014;Boppy et al, 2022;Carr & Wahlich, 1990;Ettaboina, Katakam, & Dongala, 2022;Ettaboina, Nakkala, & Chathalingath, 2022;ICH, 2003;Katakam, Ettaboina, & Dongala, 2021;Katakam, Ettaboina, & Marisetti, 2021;Lakka & Goswami, 2012;Lakka et al, 2021Lakka et al, , 2022Lakkireddy et al, 2015;Mohan et al, 2022;Nagulancha et al, 2023;Narasimha et al, 2011Narasimha et al, , 2020Narasimha et al, , 2022Siva et al, 2022;Snyder et al, 2010)…”
mentioning
confidence: 99%